Cemexi C2008, descripción de trigo duro-macarronero para su cultivo en el DDR 014, Río Colorado - Alvarado Padilla Jorge Iván; Camacho Casas, Miguel Alfonso; Chávez Vallalba Gabriela; Figueroa López Pedro; Ávila Casillas Eva; Camarillo Pulido, Mario (Revista Mexicana de Ciencias Agrícolas, 2018)
Wheat is the main crop sown in the autumn-winter in Irrigation District 014 Colorado River (ID 014), comprising the Valley of Mexicali, BC and San Luis Río Colorado, Sonora (Hernández, et al. 2010). In the last f ive years (2008- 2012) in wheat sowing ID 014 averaged 96 975 hectares (OEIDRUS, 2013), 83.9% corresponds to the Mexicali Valley, BC between 2011 and 2013 were planted on average 58 341 hectares of durum wheat (Triticum durum Desf), with varieties Rafi C97, 19.6%, Río Colorado C2000, 18.4% and Atil C2000, 16%. The Wheat Breeding Program of the Experimental Mexicali Valley, of the National Research Institute of Forestry, Agriculture and Livestock (INIFAP), joining forces with the International Center for Maize and Wheat Improvement (CIMMYT), aims to assess and select wheat genotypes to improve the profitability and competitiveness of this crop by releasing varieties with yield, quality and health. Cemexi C2008 represents a choice of durum wheat, having a good acceptance by farmers in the Mexicali Valley, between 2011 to 2013 average planting 2695 hectares, corresponding to 3.3% of the area planted.